2017
DOI: 10.1177/2309499017718952
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant SLAP repair does not influence the surgical outcome for arthroscopic Bankart repair of traumatic shoulder dislocations

Abstract: Accompanying SLAP repair in surgical treatment with Bankart repair for shoulder instability does not affect the results negatively. Properly repaired labral tears extending from anterior inferior to the posterior superior of the glenoid in instability treatment have the same outcome in overall results as repaired isolated Bankart lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…In only 7 of 51 studies with potential eligibility were clinical outcomes adequately quantified. These 7 studies, 3,10,14,17,19,25,60 consisting of 520 patients, were included in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In only 7 of 51 studies with potential eligibility were clinical outcomes adequately quantified. These 7 studies, 3,10,14,17,19,25,60 consisting of 520 patients, were included in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] In similar studies that have compared isolated Bankart and accompanying SLAP lesions, recurrence rates of 4.2% and 8.7% have been reported. [19,20] In our study, this rate was 7.3%. There are many factors that increase the risk of recurrence after anterior instability surgery and cause unsuccessful results.…”
Section: Discussionmentioning
confidence: 42%
“…[16] The authors suggested that the bowstring effect of the labrum contributes to the maintenance of tension and anatomical reduction of the anteroinferior labrum. Aydin et al [20] advocated that repair of the anteroinferior labral lesion should occur first to perform the best reduction of the labral tears. Some studies have claimed that if the SLAP repair is performed first, it can be difficult to clearly visualize the anterior labrum, and that the "pseudolaxity" provided by the SLAP lesion improves the visibility and working space during anterior labral repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations